Genetic effects of yield and root parameters in rice (Oryza sativa L.) at reproductive stage drought stress as apportioned by generation mean analysis - Yogameenakshi, P; Vivekanandan, P; Nadarajan, N (ORYZA-An International Journal of Rice, 2019)
The nature of gene action governing important quantitative traits viz.yield and drought tolerance in rice were studied through six parameter model of generation means analysis using six generations (viz., P1, P2, F1, F2, BC1 and BC2) of five crosses by imposing drought stress at reproductive stage. Additive gene action was noticed for the traits like days to flowering, panicle length, 100 grain weight and root thickness in majority of the crosses while the yield characters like productive tillers / plant, filled grains / panicle, harvest index and grain yield / plant and the drought tolerant characters like spikelet fertility, root length and root / shoot ratio were governed by dominance gene action. Both additive and dominance effects were found in panicle length in the cross Kallurundaikar / Moroberekan; spikelet fertility, dry root weight, root/shoot ratio and grain yield / plant in the cross Norungan / Moroberekan and 100 grain weight and root thickness in the cross PMK 2 / Moroberekan. Interaction effects mainly of additive x additive was noticed in panicle length, filled grains /panicle, dry root weight and root/shoot ratio in most of the crosses while dominance x dominance gene action was predominant in 100 grain weight and both additive x dominance and dominance x dominance in days to flowering and plant height.